Higher genetic diversity on mountain tops: the role of historical and contemporary processes in shaping genetic variation in the bank vole. (17th December 2015) - Cornetti, Luca; Lemoine, Mélissa; Hilfiker, Daniela; Morger, Jennifer; Reeh, Kevin; Tschirren, Barbara
Abstract : Glacial phases during the Pleistocene caused remarkable changes in species range distributions, with inevitable genetic consequences. Specifically, during interglacial phases, when the ice melted and new habitats became suitable again, species could recolonize regions that were previously covered by ice, such as high latitudes and elevations. Based on theoretical models and empirical data, a decrease in genetic variation is predicted along recolonization routes as a result of the consecutive founder effects that characterize the recolonization process. In the present study, we assessed the relative importance of historical and contemporary processes in shaping genetic diversity and differentiation of bank vole ( Myodes glareolus) populations at different elevations in the Swiss Alps. By contrast to expectations, we found that genetic variation increased with elevation. Estimates of recent migration rates and a contrasting pattern of genetic differentiation observed at the mitochondrial cytochrome b gene and nuclear microsatellites support the hypothesis that higher genetic diversity at high elevation results from contemporary gene flow. Although historical recolonization processes can have marked effects on the genetic structure of populations, the present study provides an example where contemporary processes along an environmental gradient can reverse predicted patterns of genetic variation.